IMPLEMENTATION OF GROUP COUNSELING IN OVERCOMING CULTURE SHOCK FOR OVERSEAS STUDENTS OF UIN SUMATRA UTARA - Syafitri, Nurin; Wahyuni, Sri (TA'DIB: JURNAL PENDIDIKAN ISLAM, 2023)
This research aims to explore the application of group counseling in addressing the culture shock experienced by migrant students at UIN Sumatra Utara. The research method used is qualitative with a descriptive approach. Primary data was obtained through interviews and observations of migrant students participating in group counseling sessions. The research findings indicate that the implementation of group counseling is effective in assisting migrant students in dealing with culture shock. Through group counseling sessions, migrant students can express their problems and discomfort arising from cultural differences. Discussions and interactions with fellow migrant students and group counseling facilitators provide emotional support, understanding, and self-adjustment strategies. The application of group counseling also helps migrant students gain new insights about themselves, and the new culture, and strengthen their social skills. In this process, group support and togetherness in addressing culture shock became important factors in the success of migrant students' adjustment.